DESIGN AND BUILD INFORMATION SYSTEM FOR BPJS POLYCLINIC CLAIM FILE COMPLETENESS AT MUHAMMADIYAH HOSPITAL BANDUNG - Tsaniya Aini Yasifa; Yuda Syahidin; Leni Herfiyanti (Informatika, Universitas Jenderal Soedirman, 2022)
Completeness of medical records is vital and important in the BPJS claim process in accordance with what is stated in the practical guidelines for administering and claiming BPJS health facilities. This study aims to design an information system for the completeness of the BPJS Polyclinic claim file at the Muhammadiyah Hospital in Bandung. This study uses a qualitative analysis method with a descriptive approach and waterfall for the design development method. The Waterfall method has a clear flow, so errors can be reduced, and makes project work more detailed. The data collection technique used is by means of observation, interviews, documentation and data analysis. Some of the problems found during the observation were incomplete medical records, the process of analyzing the completeness of medical records was done manually, not reading the diagnosis written by the doctor on the medical resume, the absence of a doctor's signature, and the absence of a photocopy of the patient's identity card, for example a photocopy of ID card and photocopy of BPJS card so that there is a delay in the claim process. Therefore, an information system is needed to support the completeness of medical records so that the BPJS claim process runs correctly and smoothly. The information system that the researcher built helps PMIK in carrying out BPJS claim activities.